Negotiation, Speed, Politics: Use of Digital Technologies in International Mediation - Safiye Ateş Burç (Siyasal: Journal of Political Sciences)
The super-accelerated (high-speed) life experiences and coercive practices of the new world order (Covid and post-Covid periods) have affected and changed the negotiation and conflict resolution skills of international actors. Today, with the pandemic and technological developments, acceleration has become a necessity in many fields. Many international mediators, especially the United Nations (UN), have also benefited greatly from digital technologies that pierce space and time during the most severe times of the Covid-19 pandemic. So, in today’s world, where economic, social and technological development continues at high speed, should negotiations and policies keep pace? If so, how should accelerated and virtualised political practices be discussed over conflict resolution? What is the impact of digitalisation on international mediation? This article critically discusses the relationship between digitalisation, speed, politics and conflict resolution through content and discourse analysis of political reports on peacemaking practices of different UN missions, especially during the most traumatic period of the pandemic (March 2020-March 2021). The study concludes that politics and negotiations need speed barriers because they need time, but they cannot be isolated from the developments and space of the high-speed society, so they need to follow the virtual space at all times and get involved when needed. As the analyses of the missions’ reports show, the effective use of digital technologies, especially during the pandemic, has led to a rapid transformation in mediation (from traditional to cyber-mediation) and conflict resolution activities have been able to continue uninterrupted, but the dangers of digitalisation have not disappeared.